The distribution, biota and stratigraphy of a Windsor Group limestone (Mississippian) and associated sediments in the Quaco Head area of New Brunswick - Plint, A. G.; Ryan, R. J.; van de Poll, H. W. (Atlantic Geoscience, 1983)
Re-mapping of the Quaco Head area of southern New Brunswick has shown that Windsor Group Limestones have a more extensive distribution than was previously recognized. The limestone at Quaco Head is up to 8.5 m thick and rests unconformably on basalts Precambrian (Coldbrook) age. The limestone, which now consists mainly of microsparite, shows prominent algal lamination including laterally-linked hemispheroids and large, isolated ’heads’, up to 80 cm high. Stratified and laminated limestone with a pseudo-oolitic texture occupies the troughs between the ’heads’. The limestone is capped by 2 m of calcibreccia, overlain by red, matrix supported polymict conglomerates, laminated sandy siltstones and coarse, clast-supported polymict conglomerates. The limestone lithofacies form a regressive sequence, deposited in shallow subtidal and intertidal environments, close to the shore of the Windsor sea. The overlying clastic sediments probably record the onset of vigorous siliclastic alluvial fan sedimentation in response to local fault movement in ?Late Viséan (Hopewell Group) times. RÉSUMÉ De nouveaux relevés cartographiques dans la région de Quaco Head au sud du Nouveau-Brunswick démontrent que l’étendue des calcaires du groupe Windsor est plus importante qu’on ne le croyait. Le calcaire à Quaco Head à une épaisseur de 8.5 m et repose en discordance sur des basaltes pré-cambrlens (Coldbrook). Le calcaire, qui consiste surtout de microsparite, présente des feuillets d’algues sailIants comprenant des formes hémisphériques liées. lateralement et du grandes “têtes” isolées mesurant jusqu’à 80 cm de hauteur. Un calcaire stratifie et lamelleux à texture pseudo-oolithique occupe les dépressions entre les "têtes". Le calcaire est coiffé d’une brèche calcaire de 2 à d’épaisseur et recouvert de conglomerats polygeniques rouges à matrice portante, de siltstones sableux lamelieux et de grossiers conglomerats polygeniques se soutenant. Le lithofacies calcaire constitue une séquence en regressivite déposée près du rivage de la mer Windsor, sur l’estran et en milieu peu profond. Les sédiments clastiques qui recouvrent le calcaire retire sen tent probablement le début d’une vigoureuse sédimentation siliclastlque provenant d’un cone de déjection, le résultat de mouvements de failles locales datant de (?) la fin du Viséen (groupe Hopewell). [Tradult par le Journal]